Challenges and opportunities of innovation and incubators as a tool for knowledge-based economy - Hanadi Mubarak Al-Mubaraki; Michael Busler (Journal of Innovation and Entrepreneurship, 2017)
Objectives: The purpose of this research is to analyze and identify the challenges and opportunities of innovation and incubators programs and their potential use worldwide. Prior work: Discussed innovation and incubators as a powerful tool for knowledge-based economy from different perspectives using different criteria to measure the key performance indicators of best practices for innovation in the United States (US), United Kingdom (UK), and Gulf Cooperation Council States (GCC). The results are part of the ongoing research project funded by a grant from the Kuwait Foundation for Advancement of Sciences (KFAS-2012-1103-01). Approach: The methodology is based on quantitative approach (survey questionnaire) and literature review. Results: This paper provides several recommendations for the international implementation of innovation and incubators outcomes. Implications: This paper provides value-added knowledge for both academics and practitioners who are interested in the successful adaptation of innovation and incubators. Value: The authors believe that this paper demonstrates an added value to the current literature on innovation and incubators and fills the gap in the case studies in the literature of developed and developing countries and presents a more comprehensive analysis of progress and challenges to knowledge-based economies.
Keywords: 650; Innovation; Incubators; Technology transfer; Developed countries; Knowledge-based economy; Quantitative